COVID-19 disruption and meaningful Work: the mediating role of family–work conflict - Vara Horna, Arístides Alfredo; Espinosa Domínguez, Amparo Guadalupe (Multidisciplinary Digital Publishing Institute, 2023)
Work overload and the alteration in family dynamics caused by the COVID‑19 pandemic crisis may be increasing family–work conflict, leading to the consequent decrease in meaningful work. Using the structural equation modeling of covariance, this research determines the impact of the pandemic disruption on meaningful work as mediated through family–work conflict. The sample comes from 534 men and 257 women that are full‑time employees of seven public manufacturing companies in Bolivia; they were surveyed by filling out a self‑report questionnaire at the companies’ locations. Although no significant direct effects were found between COVID‑19 disruption and meaningful work (standardized beta = 0.038, Z = 0.756, p = 0.450), there is an indirect effect when the relationship is measured through the family–work life conflict variable (standardized beta = −0.138, Z = −6.119, p < 0.001). Implications for business management are discussed.